2019
DOI: 10.1002/cphc.201900866
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Platinum Single Crystals in Acidic Medium

Abstract: Platinum single crystal basal planes consisting of Pt(111), Pt(100), Pt(110) and reference polycrystalline platinum Pt(poly) were subjected to various potentiodynamic and potentiostatic electrochemical treatments in 0.1 M HClO4. Using the scanning flow cell coupled to an inductively coupled plasma mass spectrometer (SFC‐ICP‐MS) the transient dissolution was detected on‐line. Clear trends in dissolution onset potentials and quantities emerged which can be related to the differences in the crystal plane surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 68 publications
6
43
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11] Some such studies followed these processes with potential cycling, where it is known that the surface restructuring over many cycles leads to a roughened surface, and that dissolution is enhanced during oxide reduction. [12][13][14][15][16][17][18][19][20][21][22] Explanation of this behaviour generally invokes a place exchange (PE) process, in which a Pt surface atom leaves its lattice site and oxygen penetrates into the metal lattice. On Pt(111), pioneering studies demonstrated that PE can be directly observed by surface X-ray diffraction (SXRD).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] Some such studies followed these processes with potential cycling, where it is known that the surface restructuring over many cycles leads to a roughened surface, and that dissolution is enhanced during oxide reduction. [12][13][14][15][16][17][18][19][20][21][22] Explanation of this behaviour generally invokes a place exchange (PE) process, in which a Pt surface atom leaves its lattice site and oxygen penetrates into the metal lattice. On Pt(111), pioneering studies demonstrated that PE can be directly observed by surface X-ray diffraction (SXRD).…”
Section: Introductionmentioning
confidence: 99%
“…Potential cycling leads to reproducible full range CVs. However, the surface atom arrangement is changed by the oxidation 59 and dissolution and redeposition changes the surface atom arrangement 60,61 , while different surface sites of single crystals come with different dissolution rates 62 . The surface atom rearrangement due to oxidation and dissolution above 0.8 V also changes the hydrogen adsorption profile 42,63 .…”
Section: Full Range CV Datamentioning
confidence: 99%
“…This was rationalized by the average CN of ions on each of these faces, where faces with lower CNs (namely the (110) and (111) faces) were etched more quickly than the (100) faces [ 84 ]. Conversely, it is hypothesized that octahedral shaped NPs exposing Pt(111) facets dissolve less than cubic shapes exposing Pt(100) facets in acidic environments [ 85 ]. The role of facet-dependent dissolution and bactericidal activity of NPs was also investigated.…”
Section: Surface Nanotopography Of Nms In Relation To Their Biological Activitiesmentioning
confidence: 99%